Harnessing natural products for myocardial infarction therapy: Mechanistic insights and translational opportunities - Mengmeng Li; Siyi Wang; Hanya Dong; Min Wang; Ye Sun; Yu Bi; Lixia Chen; Anam Naseem; Hai Jiang; Hua Li; Bingyou Yang; Yan Liu (Pharmacological Research)
Myocardial infarction (MI) continues to pose significant challenges in clinical treatment despite medical advancements. Natural products (NPs) derived from botanical and biological sources demonstrate considerable therapeutic potential through their ability to simultaneously address multiple pathological features of MI. This comprehensive review examines the past decade of research investigating the therapeutic effects of various classes of NPs, notably terpenoids, flavonoids, alkaloids, phenolic acids, and phenylpropanoids in MI treatment. The analysis focuses on their multifaceted mechanisms of action, particularly their capacity to inhibit cellular apoptosis, reduce oxidative damage, attenuate fibrotic development, suppress inflammatory pathways, stimulate vascular regeneration, and normalize calcium homeostasis. Importantly, the discussion critically addresses the current limitations hindering clinical translation of NPs therapies, specifically focusing on bioavailability challenges and insufficient target specificity. Furthermore, this review also explores innovative solutions to these obstacles, particularly the significant importance of advanced drug delivery technologies and NPs for the future of personalized medicine and precision medicine. By systematically evaluating both the fundamental pharmacological properties and practical application barriers of NPs, this work provides valuable insights for future research directions in MI treatment. The synthesis of mechanistic understanding with translational considerations offers a framework for developing NPs-based therapies with improved clinical potential.